A9.04 SNPS in the baff gene are associated with increased risk of anti-jo-1-positivity and high serum baff levels in patients with myositis. (24th February 2016) - Kryštůfková, O; Svitálková, T; Hulejová, H; Světlá, M; Pleštilová, L; Pavlíková, M; Mišunová, M; Klein, M; Mann, H; Novota, P; Vencovský, J
Abstract : Background and objectives: B-cell activating factor of the TNF family (BAFF) plays a role in (auto)antibody production. Elevated serum levels (sBAFF) were found in patients with myositis. Associations of elevated sBAFF with a SNP in the 5´regulatory region of the BAFF genewere reported in patients with autoimmune diseases, together with TTTT haplotype of the four SNPs located upstream of the BAFF gene. TTTT was associated with myositis in Czech patients, independently from the HLA-DRB1*03 allele. Here we evaluate associations of sBAFF with particular SNPs, anti-Jo-1-autoantibodies, HLA-DRB1*03, ILD and disease activity in myositis. Materials and methods: The SNPs (rs9514828:871C>T, rs9514827:-2841T>C, rs3759467:-2704T>C and rs1041569:-2701T >A) were analysed by direct DNA sequencing in 311 patients with myositis (age:58.0 ± 14.5(years), females = 74%) and 113 healthy controls (age:40.6 ± 14.3, females = 70%). Levels of sBAFF were measured by ELISA. Autoantibodies were detected by immunoprecipitation. Multivariable logistic regression model for presence of anti-Jo-1-autoantibodies and nonparametric tests for group comparisons and correlation analysis were used. Results: Analysed patients cohort included 150 DM, 139 PM, 51% ILD and 24% anti-Jo-1-positive patients. HLA-DRB1*03 was present in 45% of patients and 16% of controls. Higher s-BAFF levels were detected in: patients compared to healthy controls (p < 0.0001), patients with anti-Jo-1-autoantibodies compared to autoantibody negative (p = 0.02), patients with early (duration≤ 6 month; n = 114) compared to late disease (p = 0.038) and were associated with creatine kinase (CK) levels (rho=0.36;p < 0.0001) and disease duration (rho=-0.2;p = 0.0007). Logistic regression model explaining 49% (McFadden R 2 =0.49) of the data variability included, besides ILD (OR = 27.24;p < 0.0001) and HLA-DRB1*03 (OR = 5.26;p = 0.0009), significant additive effect of the BAFF gene SNPs: -2841T allele (OR = 2.55;p = 0.028) and a -871TT genotype (OR = 7.75;p = 0.007). The alternative substitution of CK concentration (OR = 1.48;p = 0.175) with sBAFF (OR = 0.67; p = 0.037)lowered model stability (R 2 = 0.38). However, the additive effect of -871T allele to sBAFF levels in anti-Jo-1-positive patients compared to autoantibody-negative (higher in -871TT:p = 0.023 and -871CT:p = 0.043) and the opposite association in -2841TT genotype (higher in -2841CC: p = 0.033 and -2841CT:p = 0.068)were seen. Conclusion: In addition to ILD and HLA-DRB1*03 allele, SNPs of the promotor region of the BAFF gene, -871C >T and -2841T >C, increase the risk of having anti-Jo-1-autoantibodies and high sBAFF levels in patients with myositis. Acknowledgements: MZČR-Institutional support of research organisation-00023728.